Correlating Vocabulary and Sentence Structure Mastery to Students’ Writing Skill in Descriptive Text - Flora Christina (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2021)
The aims of the research are to find the correlation between vocabulary and sentence structure mastery towards students’ writing skill. This research also calculates how strong the correlation by analyzed and computed using Pearson Product Moment. The method used in this research is quantitative research method by implementing a correlation study research design that has three variables. The first variable is vocabulary mastery, the second is sentence structure mastery, and the third is students’ writing skill in descriptive text as dependent variable. The researcher gives three tests to 40 students. That test is given to measure student’s abilities according to the three previous variables. The result of this research is the use of correlation between vocabulary mastery and sentence structure mastery toward students’ writing skill. The finding of the research proves a moderate level of correlation. This study suggest that the students have to learn vocabulary mastery and sentence structure mastery, and the English teacher should prioritize it so students’ writing skill will improve.